On optimization of an adaptive pneumatic impact absorber – the innovative rescue cushion - Faraj, Rami; Popławski, Błażej; Gabryel, Dorian; Mikułowski, Grzegorz; Wiszowaty, Rafał (Bulletin of the Polish Academy of Sciences Technical Sciences, 2025)
The paper states a complex study on the adaptive rescue cushion and concerns a problem of efficient impact mitigation, which is present during evacuation or assurance of people conducted by fire brigades. In order to minimize negative effects of person’s fall from height an airbag system is applied. Unfortunately, until now only passive solutions have been used. As a result, loads acting on a landing person were not minimized, because passive systems are designed for predefined, extreme conditions. Since the authors proposed to introduce adaptation mechanisms into the rescue cushion, a number of issues arose. They include construction and control of release vents, taking into account the inaccuracies of estimated impact parameters, and optimization of the venting area in case the evacuated person lands outside the airbag center. All these problems were addressed within this paper and described in detail. Discussion on the system adaptation and its optimization was preceded by experimental validation of a numerical model. The energy absorbing capabilities of widely used passive rescue cushions were significantly enhanced as a result of the conducted research.